Embedding Authentication and DistortionConcealment in Images – A Noisy Channel Perspective - Qurban A Memon (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
In multimedia communication, compression of data is essential to improve transmission rate, and minimize storage space. At the same time, authentication of transmitted data is equally important to justify all these activities. The drawback of compression is that the compressed data are vulnerable to channel noise. In this paper, error concealment methodologies with ability of error detection and concealment are investigated for integration with image authentication in JPEG2000.The image authentication includes digital signature extraction and its diffusion as a watermark. To tackle noise, the error concealment technologies are modified to include edge information of the original image.This edge_image is transmitted along with JPEG2000 compressed image to determine corrupted coefficients and regions. The simulation results are conducted on test images for different values of bit error rate to judge confidence in noise reduction within the received images.